Veljka Ruzicka Kenfel (Ed). New Trends in Children’s Literature Research --Twenty-first Century Approaches –200-2012. (2014). Spain: Peter Lang Edition. 239 pages. - Vásquez Carranza, Marina (2015)
This text incorporates various studies by researchers who belong to the group Anglo-German Children’s Literature and its Translation at the University of Vigo, first set up in 1992. The main focus is to describe new tendencies within literature for children and young adults, including translation, adaptation, comics, and palindrome.